An environmentally friendly release paper and its preparation method
Patent Information
- Application Number
- CN202610962207.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-30
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]采用上述方法制备的离型纸,各层之间主要依靠物理吸附作用结合,层间结合强度不足,使用过程中受外力牵拉或温度变化时,易出现离型层脱落、淋膜层与基纸分离的现象,离型纸的整体结构强度存在提升空间
本环保离型纸采用氨基化基纸层、淋膜层与光固化离型层依次层叠的结构,可通过层间化学反应提升结合强度。氨基化基纸表面的伯氨基能够与淋膜层中的环氧基团发生交联反应,淋膜体系中引入的不饱和双键可在紫外固化阶段与光固化离型层中的双键发生共聚,同时离型层中的异氰酸酯基团可与淋膜层的羟基发生加成反应,多重化学键合作用提升层间结合度,增强离型纸整体结构稳定性,降低分层脱落风险。基纸以原木浆为基底并负载壳聚糖成膜层,淋膜层以聚乳酸、可降解共聚酯等为主要树脂原料,二者均具备一定降解性能,可在一定程度上提升产品的环境友好性。
Smart Images

Figure SMS_1
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of release paper, in particular to an environment-friendly release paper and a preparation method thereof. BACKGROUND
[0002] Release paper is widely used in adhesive products, electronic processing and other fields. With the improvement of environmental protection requirements, degradable environment-friendly release paper has become the research direction of the industry. The existing environment-friendly release paper mostly adopts a laminated structure of base paper and film coating layer. The base paper mainly uses paper fibers as the main body and has degradable properties. The film coating layer uses degradable polyester materials such as polylactic acid and polybutylene adipate terephthalate to replace traditional non-degradable polyethylene film, so that the whole release paper has certain degradable ability and reduces the impact on the environment after being discarded.
[0003] The preparation of traditional release paper usually adopts a step-by-step coating process. The film coating resin is first coated on the surface of the base paper after being melted and extruded, and then the film coating layer is formed after cooling and setting. Then the release agent is prepared into a coating liquid and uniformly coated on the surface of the film coating layer by coating equipment. After drying and curing treatment, the release layer is formed, and finally the finished product is obtained. Part of the process will perform surface treatment on the base paper to improve the spreading effect of the film coating resin, but the treatment process mainly optimizes the surface wetting performance.
[0004] The release paper prepared by the above method is mainly combined between layers by physical adsorption, and the interlayer bonding strength is insufficient. During use, the release layer is easily separated, the film coating layer is separated from the base paper, and the overall structural strength of the release paper needs to be improved. SUMMARY
[0005] In view of the technical defects in the background art, the present application provides an environment-friendly release paper and a preparation method thereof, which solves the above technical problems and meets the actual needs. The specific technical scheme is as follows: An environment-friendly release paper comprises an aminated base paper layer, a film coating layer and a photocured release layer which are laminated in sequence. The raw material components of the film coating layer include, in parts by weight: polylactic acid 100 parts, polybutylene adipate terephthalate 40-50 parts, degradable unsaturated copolyester 15-25 parts, epoxy soybean oil 10-15 parts, double bond modified calcium carbonate whisker 10-18 parts, polycaprolactone triol 10-16 parts, free radical inhibitor 0.02 parts, antioxidant 0.5-1 parts, and lubricant 0.5-1 parts. The raw material components of the photocured release layer include: modified silicone oil 100 parts, photoinitiator 2 parts, and anhydrous ethyl acetate 40-50 parts.
[0006] As a further technical scheme of the present application, the aminated base paper layer has a basis weight of 60-80 g / m 2The base is made of virgin wood pulp paper, and the surface is loaded with a chitosan film layer with a deacetylation degree of ≥90%.
[0007] As a further technical solution of the present invention, the biodegradable unsaturated copolyester is poly(butylene succinate-co-itaconic acid butylene glycol ester) with an intrinsic viscosity of 0.9-1.1 dL / g, the polycaprolactone triol has a molecular weight of 1000-2000; the free radical inhibitor is hydroquinone, the antioxidant is antioxidant 1010, and the lubricant is calcium stearate.
[0008] A method for preparing environmentally friendly release paper includes the following steps: S1. Prepare a treatment solution containing amino polymers, immerse the virgin wood pulp paper in the treatment solution for impregnation treatment, remove it, remove excess liquid and dry it to obtain an amino-based paper with primary amino groups on the surface. S2. Calcium carbonate whiskers are dispersed in an alcohol-water mixture, and a silane coupling agent containing double bonds is added to carry out a grafting reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain double bond modified calcium carbonate whiskers. Saturated diacid, unsaturated diacid and diol are mixed in proportion, and after adding a catalyst, esterification reaction is carried out first under inert gas protection, followed by compression polymerization reaction to obtain biodegradable unsaturated copolyester. S3. The resin raw materials of the coating layer are pre-vacuum dried, then mixed with double bond modified calcium carbonate whiskers, polycaprolactone triol, free radical inhibitor, antioxidant and lubricant, and put into the extrusion equipment for melt blending. After extrusion and cooling, the mixture is granulated to obtain the coating composite masterbatch. S4. After mixing the cyclosiloxane monomer with the end-capping agent, vacuum dehydration is performed. Under inert gas protection, an alkaline catalyst is added, and double-bonded silanes and hydroxyl-containing silanes are slowly added dropwise to carry out a ring-opening copolymerization reaction. After the reaction is completed, an acid is added to neutralize and terminate the reaction. The low-boiling substances and residual monomers are removed by heating and depressurization to obtain the precursor silicone oil. The precursor silicone oil is dissolved in an anhydrous solvent, and diisocyanate and catalyst are added. An addition reaction is carried out under inert gas protection. After the reaction, the solvent and residual free monomers are removed by depressurization to obtain the modified silicone oil. S5. Mix the modified silicone oil, photoinitiator and anhydrous solvent evenly to prepare a photocurable release agent; heat and melt the coating composite masterbatch and extrude it onto the surface of the aminated base paper, cool and shape it to form a coating layer; coat the surface of the coating layer with the photocurable release agent, dry it to remove the solvent and then irradiate it with ultraviolet light; after curing, roll up the release paper and place it in a constant temperature environment to mature, and obtain the finished environmentally friendly release paper.
[0009] As a further technical solution of the present invention, step S1 is specifically operated as follows: by mass, 2 parts of chitosan are dissolved in 98 parts of deionized water, 0.8 parts of glacial acetic acid are added dropwise, and the mixture is stirred until completely dissolved to obtain a chitosan solution; the virgin wood pulp paper is immersed in the chitosan solution for 2 minutes, and after being taken out, it is rolled to remove excess liquid and dried at 65±5℃ to make chitosan uniformly form a film on the fiber surface, thereby obtaining an aminated base paper with a surface rich in primary amino groups.
[0010] As a further technical solution of the present invention, step S2 specifically includes: Step S21: Preparation of double-bond modified calcium carbonate whiskers: 20g of calcium carbonate whiskers with an aspect ratio of 10-20 were ultrasonically dispersed in 200mL of an ethanol / water mixture with a volume ratio of 9:1. 1.5g of silane coupling agent KH-570 was added, and the pH was adjusted to 4-5 with acetic acid. The mixture was stirred at 60℃ for 2h. After filtration, washing with ethanol, and vacuum drying at 80℃, double-bond modified calcium carbonate whiskers were obtained. Step S22: Synthesis of biodegradable unsaturated copolyester: 0.8 mol succinic acid, 0.2 mol itaconic acid, 1.05 mol 1,4-butanediol and tetrabutyl titanate catalyst at 0.05 mol% relative to the amount of acid were added to the reactor. The esterification reaction was carried out at 180℃ for 2 h under nitrogen protection, followed by polycondensation reaction at 220℃ under reduced pressure for 3 h to obtain poly(butylene succinate-co-butylene itaconic acid).
[0011] As a further technical solution of the present invention, step S3 specifically includes: Polylactic acid and polybutylene adipate terephthalate were vacuum dried at 60℃ for 8 hours, biodegradable unsaturated copolyester was vacuum dried at 40℃ for 12 hours, and polycaprolactone triol was vacuum dried at 80℃ for 2 hours and then sealed and cooled. All coating layer raw materials were added to a high-speed mixer and thoroughly mixed. The mixture was then fed into a twin-screw extruder and melt-blended at 150-180℃, extruded and granulated to obtain the coating composite masterbatch.
[0012] As a further technical solution of the present invention, step S4 specifically includes: Step S41: By weight, add 100 parts of a dimethylcyclosiloxane mixture and 0.6-0.9 parts of the end-capping agent hexamethyldisiloxane into a reaction vessel, heat to 45°C, dehydrate under a vacuum of -0.095 MPa for 30 min, and purge with nitrogen for protection; add 0.5-1 parts of 2% tetramethylammonium hydroxide alkali gel, stir evenly, and slowly add 14-18 parts of a mixture of 3-(diethoxymethylsilyl)propyl 2-acrylate and 8-12 parts of 3-hydroxypropylmethyldiethoxysilane, and complete the addition in 1 h; after the addition is complete, keep the reaction at 48-50°C for 4.5 h; add glacial acetic acid to neutralize to pH=6.5-7.0, stir for 30 min to terminate the reaction; heat to 125°C, and remove low-boiling substances and residual monomers by vacuum distillation under a vacuum of ≤80 Pa to obtain the precursor silicone oil; Step S42: Dissolve 100 parts by mass of precursor silicone oil in an equal mass of anhydrous ethyl acetate, add isophorone diisocyanate at a -NCO / -OH molar ratio of 1.8-2.2:1, and then add 0.05-0.1 parts of dibutyltin dilaurate catalyst; slowly heat to 60-65℃ under nitrogen protection and stir at a constant temperature for 3-4 hours; after the reaction is completed, evaporate ethyl acetate and residual free monomers under reduced pressure at 60℃ to obtain modified silicone oil.
[0013] As a further technical solution of the present invention, step S5 specifically includes: By weight, 100 parts modified silicone oil, 2 parts photoinitiator Irgacure 651, and 40-50 parts anhydrous ethyl acetate are mixed evenly under anhydrous and light-protected conditions to prepare a photocurable release agent. Using a casting coating machine, the coating composite masterbatch is melt-extruded at 170-190℃ and evenly coated onto the surface of the aminated base paper, with the coating thickness controlled at 15-25μm. After cooling and setting, the photocurable release agent is coated onto the surface of the coating layer using an anilox roller, with a wet film thickness of 1-3μm. After drying at 40-50℃ to remove the solvent, it is immediately cured under ultraviolet light. The photocured release paper is then rolled up and placed in a drying oven at 40-50℃ for 24 hours to obtain environmentally friendly release paper.
[0014] The beneficial effects of this invention are as follows: This environmentally friendly release paper employs a structure consisting of an aminated base paper layer, a coating layer, and a UV-cured release layer, which enhances bonding strength through interlayer chemical reactions. The primary amino groups on the surface of the aminated base paper can cross-link with the epoxy groups in the coating layer. Unsaturated double bonds introduced into the coating system can copolymerize with double bonds in the UV-cured release layer during the UV curing stage. Simultaneously, isocyanate groups in the release layer can undergo addition reactions with hydroxyl groups in the coating layer. This multi-layered chemical bonding enhances interlayer adhesion, strengthens the overall structural stability of the release paper, and reduces the risk of delamination. The base paper uses wood pulp as a substrate and is loaded with a chitosan film layer. The coating layer uses polylactic acid and biodegradable copolyester as the main resin raw materials; both possess certain biodegradability, which can improve the product's environmental friendliness to a certain extent. Detailed Implementation
[0015] The embodiments of the present invention will be described below with reference to relevant examples. The embodiments of the present invention are not limited to those described below, and the present invention relates to necessary knowledge in this technical field. It should be considered as well-known technology in this technical field, and is known and mastered by those skilled in the art. Experimental methods in the following examples that do not specify specific conditions are generally performed under conventional conditions in the art or according to the manufacturer's recommendations. Unless otherwise specified, the raw materials and reagents used are all commercially available from the conventional market. Any non-substantial changes and substitutions made by those skilled in the art based on the present invention are within the scope of protection claimed by the present invention.
[0016] An environmentally friendly release paper comprises an aminated base paper layer, a coating layer, and a photocurable release layer stacked sequentially. By weight, the raw material components of the coating layer include: 100 parts polylactic acid, 40-50 parts polybutylene adipate terephthalate, 15-25 parts biodegradable unsaturated copolyester, 10-15 parts epoxidized soybean oil, 10-18 parts double-bond modified calcium carbonate whiskers, 10-16 parts polycaprolactone triol, 0.02 parts free radical inhibitor, 0.5-1 part antioxidant, and 0.5-1 part lubricant. The raw material components of the photocurable release layer include: 100 parts modified silicone oil, 2 parts photoinitiator, and 40-50 parts anhydrous ethyl acetate.
[0017] The coating layer of this invention uses polylactic acid as the base resin, combined with polybutylene adipate terephthalate (PEG) to adjust the toughness of the matrix. The addition of biodegradable unsaturated copolyester introduces unsaturated double bond structures into the resin matrix, providing reaction sites for interlayer crosslinking. Epoxidized soybean oil improves the plasticizing effect of the resin system and enhances processing fluidity. The epoxy groups in its molecules can react with the amino groups of the aminated base paper layer to form an interfacial bond. Double bond modified calcium carbonate whiskers are dispersed in the resin matrix to improve the mechanical strength and dimensional stability of the coating layer. The carbon double bonds on the surface of the whiskers can participate in the crosslinking reaction with the carbon double bonds of the photocured release layer, enhancing the bonding effect between the filler and the resin. Polycaprolactone triol has multiple hydroxyl groups, which can adjust the flexibility of the resin system and provide reaction sites for the isocyanate groups of the release layer. Free radical inhibitors control the degree of double bond reaction during processing, avoiding the influence of pre-crosslinking on processing performance. Antioxidants and lubricants respectively improve the thermal stability and processing release effect of the system.
[0018] The photocurable release layer is primarily composed of modified silicone oil. Upon exposure to ultraviolet light, it undergoes cross-linking and curing to form the release surface. Simultaneously, the carbon double bonds in the molecule can copolymerize with the unsaturated double bonds on the surface of the coating layer, and the isocyanate groups can undergo addition reactions with the hydroxyl groups in the coating layer. The combined effect of these multiple chemical bonds enhances the bonding strength between the release layer and the coating layer, reducing the possibility of release layer detachment. The primary amino groups on the surface of the aminated base paper layer can undergo ring-opening reactions with the epoxy groups in the coating layer, forming chemical bonds between the base paper and the coating layer, thus increasing the interlayer bonding strength. Both the base paper and the coating layer are made of biodegradable materials, capable of degrading under certain conditions after disposal, reducing environmental burden. The chemical cross-linking between the layers forms a stable whole, ensuring the structural stability of the release paper during use.
[0019] As one of the preferred embodiments of the present invention, the aminated paper layer has a basis weight of 60-80 g / m³. 2 The base is made of virgin wood pulp paper, and the surface is loaded with a chitosan film layer with a deacetylation degree of ≥90%.
[0020] Specifically, the aminated base paper layer uses a basis weight of 60-80 g / m³. 2 Using raw wood pulp paper as the base, a chitosan film layer with a deacetylation degree ≥90% is loaded on the surface. The high deacetylation degree allows the chitosan molecules to carry sufficient primary amino groups, which can be evenly distributed on the surface of the paper base fiber, providing reaction sites for the subsequent ring-opening reaction with the epoxy groups in the coating layer, thus realizing the chemical bonding between the base paper and the coating layer.
[0021] As one of the preferred embodiments of the present invention, the biodegradable unsaturated copolyester is poly(butylene succinate-co-itaconic acid butylene glycol ester) with an intrinsic viscosity of 0.9-1.1 dL / g, the polycaprolactone triol has a molecular weight of 1000-2000, the free radical inhibitor is hydroquinone, the antioxidant is antioxidant 1010, and the lubricant is calcium stearate.
[0022] Specifically, poly(butylene succinate-co-butylene itaconic acid), as a biodegradable unsaturated copolyester, introduces unsaturated double bonds into its molecular chain through its itaconic acid structure. Its intrinsic viscosity of 0.9-1.1 dL / g corresponds to a moderate molecular weight, which ensures compatibility with polylactic acid and polybutylene adipate-terephthalate, provides sufficient reaction sites for the system, and is itself biodegradable.
[0023] Polycaprolactone triol with a molecular weight of 1000-2000 has a multi-hydroxyl structure, which can adjust the flexibility of the resin matrix. Simultaneously, the terminal hydroxyl groups can react with the isocyanate groups of the release layer, strengthening the interlayer bonding effect. Hydroquinone, as a free radical inhibitor, can capture free radicals in the high-temperature environment of melt blending, inhibiting premature cross-linking of double bonds and maintaining the processing flowability of the material. Antioxidant 1010 can reduce the thermal oxidative degradation of the resin during high-temperature processing, while calcium stearate reduces friction between the melt and processing equipment, improving material flow and demolding performance.
[0024] A method for preparing environmentally friendly release paper includes the following steps: S1. Prepare a treatment solution containing amino polymers, immerse the virgin wood pulp paper in the treatment solution for impregnation treatment, remove it, remove excess liquid and dry it to obtain an amino-based paper with primary amino groups on the surface. S2. Calcium carbonate whiskers are dispersed in an alcohol-water mixture, and a silane coupling agent containing double bonds is added to carry out a grafting reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain double bond modified calcium carbonate whiskers. Saturated diacid, unsaturated diacid and diol are mixed in proportion, and after adding a catalyst, esterification reaction is carried out first under inert gas protection, followed by compression polymerization reaction to obtain biodegradable unsaturated copolyester. S3. The resin raw materials of the coating layer are pre-vacuum dried, then mixed with double bond modified calcium carbonate whiskers, polycaprolactone triol, free radical inhibitor, antioxidant and lubricant, and put into the extrusion equipment for melt blending. After extrusion and cooling, the mixture is granulated to obtain the coating composite masterbatch. S4. After mixing the cyclosiloxane monomer with the end-capping agent, vacuum dehydration is performed. Under inert gas protection, an alkaline catalyst is added, and double-bonded silanes and hydroxyl-containing silanes are slowly added dropwise to carry out a ring-opening copolymerization reaction. After the reaction is completed, an acid is added to neutralize and terminate the reaction. The low-boiling substances and residual monomers are removed by heating and depressurization to obtain the precursor silicone oil. The precursor silicone oil is dissolved in an anhydrous solvent, and diisocyanate and catalyst are added. An addition reaction is carried out under inert gas protection. After the reaction, the solvent and residual free monomers are removed by depressurization to obtain the modified silicone oil. S5. Mix the modified silicone oil, photoinitiator and anhydrous solvent evenly to prepare a photocurable release agent; heat and melt the coating composite masterbatch and extrude it onto the surface of the aminated base paper, cool and shape it to form a coating layer; coat the surface of the coating layer with the photocurable release agent, dry it to remove the solvent and then irradiate it with ultraviolet light; after curing, roll up the release paper and place it in a constant temperature environment to mature, and obtain the finished environmentally friendly release paper.
[0025] In the preparation method of the present invention, step S1 uses an impregnation process to load a chitosan film layer on the surface of virgin wood pulp paper. The operating conditions are mild, which allows the chitosan to be evenly distributed on the fiber surface, introducing stable primary amino active sites into the paper base and providing a reaction basis for subsequent interfacial bonding with the coating layer. In step S2, double-bond modified calcium carbonate whiskers and biodegradable unsaturated copolyester are prepared respectively. After the whiskers are grafted with a silane coupling agent, they have double bonds on their surface, which can improve the bonding effect with the resin matrix. The biodegradable unsaturated copolyester obtained by in-situ polymerization takes into account both blend compatibility and reactivity.
[0026] Step S3 involves melt-blending the dried raw materials to produce a masterbatch. Pre-vacuum drying reduces the degree of hydrolysis during high-temperature resin processing. Twin-screw blending ensures uniform dispersion of resin, filler, and additives. Free radical inhibitors prevent premature cross-linking of double bonds within the system, maintaining melt processing fluidity. The resulting masterbatch is easy to store and use. Step S4 involves a two-step reaction to prepare modified silicone oil. First, double bonds and hydroxyl groups are introduced onto the siloxane chain through ring-opening copolymerization. Then, isocyanate groups are added via an addition reaction, giving the silicone oil multiple reaction sites. The reaction process parameters are controllable, and the product performance is stable.
[0027] Step S5 sequentially completes the coating process, release layer coating, and UV curing. During the melt coating process, the epoxy groups in the coating can undergo ring-opening reactions with the amino groups on the surface of the base paper. During the UV curing stage, the double bonds of the release layer and the coating layer copolymerize, and the isocyanate groups and hydroxyl groups undergo addition reactions. The curing process allows the cross-linking reaction to proceed fully, and finally, a stable chemical bond is formed between the three layers, which improves the overall structural strength of the release paper. The process is seamless and suitable for continuous production.
[0028] As one of the preferred embodiments of the present invention, step S1 is specifically operated as follows: by mass, 2 parts of chitosan are dissolved in 98 parts of deionized water, 0.8 parts of glacial acetic acid are added dropwise, and the mixture is stirred until completely dissolved to obtain a chitosan solution; the virgin wood pulp paper is immersed in the chitosan solution for 2 minutes, and after being taken out, it is rolled to remove excess liquid and dried at 65±5℃ to make chitosan uniformly form a film on the fiber surface, thereby obtaining an aminated base paper with a surface rich in primary amino groups.
[0029] Specifically, glacial acetic acid is used to adjust the pH of the solution, protonating the amino groups in the chitosan molecules to achieve uniform dissolution of chitosan in water and form a stable treatment solution. Impregnation of the virgin wood pulp paper for 2 minutes ensures the treatment solution fully wets the fiber surface and internal pores. Rolling removes excess liquid, controlling the chitosan loading. Drying is then carried out at 65±5℃, allowing the solvent to slowly evaporate. This results in a continuous and uniform film of chitosan on the fiber surface, fully exposing the primary amino groups on the molecular chains, providing active sites for subsequent reactions with the epoxy groups of the coating layer. Simultaneously, the chitosan and paper fibers are stably bonded.
[0030] As one of the preferred embodiments of the present invention, step S2 specifically includes: Step S21: Preparation of double-bond modified calcium carbonate whiskers: 20g of calcium carbonate whiskers with an aspect ratio of 10-20 were ultrasonically dispersed in 200mL of an ethanol / water mixture with a volume ratio of 9:1. 1.5g of silane coupling agent KH-570 was added, and the pH was adjusted to 4-5 with acetic acid. The mixture was stirred at 60℃ for 2h. After filtration, washing with ethanol, and vacuum drying at 80℃, double-bond modified calcium carbonate whiskers were obtained. Step S22: Synthesis of biodegradable unsaturated copolyester: 0.8 mol succinic acid, 0.2 mol itaconic acid, 1.05 mol 1,4-butanediol and tetrabutyl titanate catalyst at 0.05 mol% relative to the amount of acid were added to the reactor. The esterification reaction was carried out at 180℃ for 2 h under nitrogen protection, followed by polycondensation reaction at 220℃ under reduced pressure for 3 h to obtain poly(butylene succinate-co-butylene itaconic acid).
[0031] Specifically, in step S21, ethanol and water are mixed in a 9:1 ratio, and the pH is adjusted to 4-5 to promote the hydrolysis of KH-570 to generate silanol groups. The mixture is reacted at 60°C for 2 hours, during which the silanol groups condense and graft with the hydroxyl groups on the surface of the calcium carbonate whiskers, introducing a double bond structure onto the whisker surface. After washing to remove unreacted coupling agent, the whiskers are vacuum dried to obtain modified whiskers, which can improve the subsequent interfacial bonding effect with the resin matrix.
[0032] In step S22, succinic acid and itaconic acid are combined with 1,4-butanediol in a specific ratio and undergo an esterification reaction at 180°C under the catalysis of tetrabutyl titanate. The acid and alcohol form ester bonds and remove water. A nitrogen atmosphere prevents high-temperature oxidation of the raw materials. Subsequently, polycondensation is carried out under reduced pressure at 220°C to remove small molecules and lengthen the molecular chain. The unsaturated double bonds in the itaconic acid structure are retained in the molecular chain, ultimately yielding a biodegradable unsaturated copolyester that combines biodegradability and double bond reactivity.
[0033] As one of the preferred embodiments of the present invention, step S3 specifically involves: drying polylactic acid and polybutylene adipate-terephthalate under vacuum at 60°C for 8 hours, drying the biodegradable unsaturated copolyester under vacuum at 40°C for 12 hours, and drying polycaprolactone triol under vacuum at 80°C for 2 hours, followed by sealing and cooling; adding all the coating layer raw materials to a high-speed mixer for thorough mixing, feeding them into a twin-screw extruder, and melt-blending and extruding granulation at 150-180°C to obtain the coating composite masterbatch.
[0034] Differentiated vacuum drying parameters were applied to polylactic acid, polybutylene adipate-terephthalate, biodegradable unsaturated copolyester, and polycaprolactone triol to remove residual moisture and prevent hydrolysis of polyester materials during melt processing. High-speed mixing ensured the initial uniform dispersion of resin, filler, and various additives. The twin-screw extruder completed melt blending in the 150-180℃ range, ensuring full melting and plasticization of the matrix resin. Combined with free radical inhibitors in the system, premature cross-linking of unsaturated double bonds was prevented, maintaining melt processing fluidity. After extrusion and pelletizing, a uniformly dispersed and stable coated composite masterbatch was obtained.
[0035] As one of the preferred embodiments of the present invention, step S4 specifically includes: Step S41: By weight, add 100 parts of a dimethylcyclosiloxane mixture and 0.6-0.9 parts of the end-capping agent hexamethyldisiloxane into a reaction vessel, heat to 45°C, dehydrate under a vacuum of -0.095 MPa for 30 min, and purge with nitrogen for protection; add 0.5-1 parts of 2% tetramethylammonium hydroxide alkali gel, stir evenly, and slowly add 14-18 parts of a mixture of 3-(diethoxymethylsilyl)propyl 2-acrylate and 8-12 parts of 3-hydroxypropylmethyldiethoxysilane, and complete the addition in 1 h; after the addition is complete, keep the reaction at 48-50°C for 4.5 h; add glacial acetic acid to neutralize to pH=6.5-7.0, stir for 30 min to terminate the reaction; heat to 125°C, and remove low-boiling substances and residual monomers by vacuum distillation under a vacuum of ≤80 Pa to obtain the precursor silicone oil; Step S42: Dissolve 100 parts by mass of precursor silicone oil in an equal mass of anhydrous ethyl acetate, add isophorone diisocyanate at a -NCO / -OH molar ratio of 1.8-2.2:1, and then add 0.05-0.1 parts of dibutyltin dilaurate catalyst; slowly heat to 60-65℃ under nitrogen protection and stir at a constant temperature for 3-4 hours; after the reaction is completed, evaporate ethyl acetate and residual free monomers under reduced pressure at 60℃ to obtain modified silicone oil.
[0036] Specifically, step S41 employs an alkaline-catalyzed ring-opening copolymerization process. Pre-vacuum dehydration eliminates the interference of moisture on the ring-opening reaction, and hexamethyldisiloxane is used as a capping agent to regulate the molecular weight of the silicone oil. The slow dropwise addition of silane monomers containing double bonds and hydroxyl groups allows functional groups to be uniformly integrated into the siloxane backbone. A low-temperature reaction at 48-50℃ avoids thermal polymerization of the double bonds. Glacial acetic acid neutralizes and terminates the catalyst activity, while high-temperature, reduced-pressure removal removes low-boiling substances and residual monomers, yielding a precursor silicone oil containing both double bonds and hydroxyl groups.
[0037] Step S42 involves the addition reaction of isocyanate and hydroxyl groups. Isophorone diisocyanate is added at a predetermined molar ratio, allowing some isocyanate groups to react with the hydroxyl groups of the precursor silicone oil, while the remaining isocyanate groups remain on the molecular chain. The reaction is catalyzed by dibutyltin dilaurate, with the reaction rate controlled at a constant temperature of 60-65℃. After the reaction, the solvent and free monomer are removed under reduced pressure to obtain a modified silicone oil containing both double bonds and isocyanate groups, providing reaction sites for subsequent interlayer crosslinking.
[0038] As one of the preferred embodiments of the present invention, step S5 specifically includes: By weight, 100 parts modified silicone oil, 2 parts photoinitiator Irgacure 651, and 40-50 parts anhydrous ethyl acetate are mixed evenly under anhydrous and light-protected conditions to prepare a photocurable release agent. Using a casting coating machine, the coating composite masterbatch is melt-extruded at 170-190℃ and evenly coated onto the surface of the aminated base paper, with the coating thickness controlled at 15-25μm. After cooling and setting, the photocurable release agent is coated onto the surface of the coating layer using an anilox roller, with a wet film thickness of 1-3μm. After drying at 40-50℃ to remove the solvent, it is immediately cured under ultraviolet light. The photocured release paper is then rolled up and placed in a drying oven at 40-50℃ for 24 hours to obtain environmentally friendly release paper.
[0039] Specifically, preparing the photocurable release agent under anhydrous and light-protected conditions can prevent premature decomposition of the photoinitiator by light exposure and also prevent the isocyanate groups from reacting and becoming inactive upon contact with water. The coating composite masterbatch is melt-extruded at 170-190℃ to form a uniform coating layer on the surface of the aminated base paper. During the melt contact process, the epoxy groups in the coating layer can undergo ring-opening reactions with the primary amines on the base paper surface, improving the interfacial bonding between the two layers. Using anilox roller coating allows for precise control of the wet film thickness of the release layer. Drying at 40-50℃ gently removes the ethyl acetate solvent, preventing defects such as uneven leveling in the coating. Then, under ultraviolet light irradiation, the photoinitiator decomposes to generate free radicals, initiating copolymerization and crosslinking of the modified silicone oil itself and the double bonds on the coating layer surface. After winding, curing at 40-50℃ for 24 hours allows for sufficient crosslinking reactions between layers, stabilizing the interlayer bonding strength and release performance of the release paper.
[0040] The present invention will be further described below through examples and comparative examples. Example 1
[0041] S1. Preparation of Aminated Base Paper: Dissolve 2 parts by weight of chitosan with a degree of deacetylation of 92% in 98 parts by weight of deionized water, add 0.8 parts by weight of glacial acetic acid, and stir until completely dissolved to obtain a chitosan treatment solution; take a quantitative amount of 70 g / m³... 2 The raw wood pulp paper is immersed in the treatment solution for 2 minutes, then removed and rolled to remove excess liquid. It is then dried at 65±5℃ to allow chitosan to form a uniform film on the fiber surface, resulting in aminated base paper with a surface rich in primary amino groups.
[0042] S2. Preparation of double-bond modified calcium carbonate whiskers: 20g of calcium carbonate whiskers with an aspect ratio of 10-20 were ultrasonically dispersed in 200mL of ethanol / water mixture with a volume ratio of 9:1. 1.5g of silane coupling agent KH-570 was added, and the pH was adjusted to 4-5 with acetic acid. The mixture was stirred at 60℃ for 2h, filtered, washed with ethanol, and dried under vacuum at 80℃ to obtain double-bond modified calcium carbonate whiskers.
[0043] Synthesis of biodegradable unsaturated copolyester: 0.8 mol succinic acid, 0.2 mol itaconic acid, 1.05 mol 1,4-butanediol and 0.05 mol% tetrabutyl titanate catalyst relative to the amount of acid were added to a reactor. The esterification reaction was carried out at 180℃ for 2 h under nitrogen protection, followed by polycondensation reaction at 220℃ under reduced pressure for 3 h to obtain poly(butylene succinate-co-butylene itaconic acid) with an intrinsic viscosity of 1.0 dL / g.
[0044] S3. Preparation of the coating composite masterbatch: By weight, 100 parts of polylactic acid and 45 parts of polybutylene adipate-terephthalate were vacuum dried at 60℃ for 8 hours; 20 parts of the above-mentioned biodegradable unsaturated copolyester were vacuum dried at 40℃ for 12 hours; and 14 parts of polycaprolactone triol (molecular weight 1500) were vacuum dried at 80℃ for 2 hours, followed by sealing and cooling. The dried resin raw materials, 12 parts of epoxidized soybean oil, 14 parts of double bond modified calcium carbonate whiskers obtained in step S2, 14 parts of polycaprolactone triol, 0.02 parts of hydroquinone, 0.8 parts of antioxidant 1010, and 0.8 parts of calcium stearate were added to a high-speed mixer and thoroughly mixed. The mixture was then fed into a twin-screw extruder and melt-blended at 150-180℃ (temperature range 155-175℃), extruded and granulated to obtain the coating composite masterbatch.
[0045] S4. Preparation of modified silicone oil: Step S41: According to the mass ratio, 100 parts of the dimethylcyclosiloxane mixture and 0.8 parts of the end-capping agent hexamethyldisiloxane are added to the reaction vessel, heated to 45°C, and dehydrated for 30 min under a vacuum of -0.095 MPa, with nitrogen protection; 0.8 parts of 2% tetramethylammonium hydroxide alkali gel are added, and after stirring evenly, a mixture of 16 parts of 3-(diethoxymethylsilyl)propyl 2-acrylate and 10 parts of 3-hydroxypropylmethyldiethoxysilane is slowly added dropwise, and the addition is completed in 1 h; after the addition is completed, the reaction is kept at 48-50°C for 4.5 h; glacial acetic acid is added to neutralize to pH=6.5-7.0, and the reaction is terminated by stirring for 30 min; the temperature is raised to 125°C, and low-boiling substances and residual monomers are removed by vacuum distillation under a vacuum of ≤80 Pa to obtain the precursor silicone oil.
[0046] Step S42: Dissolve 100 parts of precursor silicone oil in an equal mass of anhydrous ethyl acetate, add isophorone diisocyanate at a -NCO / -OH molar ratio of 2.0:1, and then add 0.08 parts of dibutyltin dilaurate catalyst; slowly heat to 60-65℃ under nitrogen protection and stir at a constant temperature for 3.5h; after the reaction is completed, evaporate ethyl acetate and residual free monomers under reduced pressure at 60℃ to obtain modified silicone oil.
[0047] S5. Release Paper Forming: Under anhydrous and light-protected conditions, 100 parts modified silicone oil, 2 parts photoinitiator Irgacure 651, and 45 parts anhydrous ethyl acetate are mixed evenly to prepare a photocurable release agent. Using a casting coating machine, the coating composite masterbatch is melt-extruded at 180°C and evenly coated onto the surface of the aminated base paper from step S1, with a coating thickness controlled at 20 μm. After cooling and setting, a coating layer is formed. The photocurable release agent is then applied to the surface of the coating layer using an anilox roller, with a wet film thickness of 2 μm. After drying at 45°C to remove the solvent, it is immediately subjected to a photocurable release agent at a main wavelength of 365 nm and an energy of 1000 mJ / cm². 2The release paper is cured under ultraviolet light; the cured release paper is then rolled up and placed in a 45℃ drying room for 24 hours to obtain environmentally friendly release paper.
[0048] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that in step S1, the base paper layer is not impregnated with chitosan, and a basis weight of 70 g / m³ is directly used. 2 The virgin wood pulp paper is used as the base paper layer, and the remaining steps and formulations are the same as in Example 1.
[0049] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that in the coating layer formulation of step S3, epoxidized soybean oil is removed, and the amount of polybutylene adipate terephthalate is increased from 45 parts to 57 parts. The other raw material types, amounts and all preparation steps are the same as in Example 1.
[0050] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is as follows: In the coating layer formulation of step S3, the biodegradable unsaturated copolyester and double bond modified calcium carbonate whiskers are removed, and the amount of polybutylene adipate terephthalate is increased from 45 parts to 79 parts, while the other raw materials and steps remain unchanged; the preparation of double bond modified calcium carbonate whiskers and the synthesis of biodegradable unsaturated copolyester are omitted in the corresponding step S2.
[0051] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that in step S4, only step S41, which prepares the precursor silicone oil, is performed, and the isophorone diisocyanate addition reaction in step S42 is not performed. The photocurable release agent (100 parts precursor silicone oil, 2 parts photoinitiator Irgacure 651, and 45 parts anhydrous ethyl acetate) is directly prepared with the obtained precursor silicone oil. All other steps are the same as in Example 1.
[0052] Comparative Example 5 The difference between Comparative Example 5 and Example 1 is that in the coating layer formulation of step S3, polycaprolactone triol is removed, and the amount of polybutylene adipate terephthalate is increased from 45 parts to 59 parts. The remaining raw materials and steps are the same as in Example 1.
[0053] Performance testing: The tear resistance of the release paper was tested according to GB / T 455 method, and the tensile strength of the release paper was tested according to GB / T 12914 method. The test results are shown in the table below:
[0054] The data in the table above shows that the tear resistance of Example 1 is 1.92 N and the tensile strength is 9.51 kN / m. Comparing the data of the comparative examples, the chemical bonding between the base paper and the coating layer has the most direct impact on the overall mechanical properties. Comparative Example 1 did not treat the base paper with chitosan with a deacetylation degree of 92%, and the surface of the base paper lacked primary amino groups. Even though the coating layer contained 12 parts of epoxy groups provided by epoxidized soybean oil, a ring-opening reaction could not occur, and the interlayer relied solely on physical adsorption. Its tear resistance and tensile strength decreased to 1.35 N and 8.45 kN / m, respectively, with the largest decrease among the comparative examples. Comparative Example 2 removed epoxidized soybean oil from the coating layer formulation, which also cut off the amino-epoxy crosslinking pathway. The degree of performance decline was similar to that of Comparative Example 1, indicating that the chemical bonding at the paper-film interface is the basis for maintaining the integrity of the release paper structure. The crosslinking between the coating layer and the release layer is achieved through two pathways: double bond copolymerization and isocyanate-hydroxyl addition. Comparative Example 3 removed the biodegradable unsaturated copolyester and double-bond modified calcium carbonate whiskers, resulting in the loss of reactive carbon-carbon double bonds on the surface of the coating layer. During photocuring, the release layer could only self-crosslink, weakening its adhesion to the coating layer and reducing its tear resistance to 1.52 N. Comparative Example 4 did not modify the precursor silicone oil with isocyanate, and the release layer lacked isocyanate groups, making it unable to react with the hydroxyl groups of polycaprolactone triol (molecular weight 1500, 14 parts) in the coating layer. The performance degradation was similar to that of Comparative Example 3. Comparative Example 5 only removed polycaprolactone triol, resulting in a significant reduction in the number of active hydroxyl groups in the coating layer. However, a small amount of ring-opening hydroxyl groups in the epoxidized soybean oil could still participate in the reaction, resulting in the smallest performance degradation.
[0055] The above description is only a preferred embodiment of the present invention. It should be noted that those skilled in the art can make several improvements and modifications without departing from the principle of the present invention, and these improvements and modifications should also be considered within the scope of protection of the present invention.
Claims
1. An environmentally friendly release paper, comprising an aminated base paper layer, a coating layer, and a photocurable release layer stacked sequentially, characterized in that, By weight, the raw material components of the coating layer include: 100 parts polylactic acid, 40-50 parts polybutylene adipate terephthalate, 15-25 parts biodegradable unsaturated copolyester, 10-15 parts epoxidized soybean oil, 10-18 parts double bond modified calcium carbonate whiskers, 10-16 parts polycaprolactone triol, 0.02 parts free radical inhibitor, 0.5-1 part antioxidant, and 0.5-1 part lubricant; The raw material components of the photocurable release layer include: 100 parts modified silicone oil, 2 parts photoinitiator, and 40-50 parts anhydrous ethyl acetate.
2. The environmentally friendly release paper according to claim 1, characterized in that, The aminated base paper layer has a basis weight of 60-80 g / m³. 2 The base is made of virgin wood pulp paper, and the surface is loaded with a chitosan film layer with a deacetylation degree of ≥90%.
3. The environmentally friendly release paper according to claim 1, characterized in that, The biodegradable unsaturated copolyester is poly(butylene succinate-co-itaconic acid butylene glycol ester) with an intrinsic viscosity of 0.9-1.1 dL / g, and the polycaprolactone triol has a molecular weight of 1000-2000; the free radical inhibitor is hydroquinone, the antioxidant is antioxidant 1010, and the lubricant is calcium stearate.
4. The method for preparing environmentally friendly release paper according to any one of claims 1 to 3, characterized in that, Includes the following steps: S1. Prepare a treatment solution containing amino polymers, immerse the virgin wood pulp paper in the treatment solution for impregnation treatment, remove it, remove excess liquid and dry it to obtain an amino-based paper with primary amino groups on the surface. S2. Calcium carbonate whiskers are dispersed in an alcohol-water mixture, and a silane coupling agent containing double bonds is added to carry out a grafting reaction. After the reaction is completed, the mixture is filtered, washed and dried to obtain double bond modified calcium carbonate whiskers. Saturated diacid, unsaturated diacid and diol are mixed in proportion, and after adding a catalyst, esterification reaction is carried out first under inert gas protection, followed by compression polymerization reaction to obtain biodegradable unsaturated copolyester. S3. The resin raw materials of the coating layer are pre-vacuum dried, then mixed with double bond modified calcium carbonate whiskers, polycaprolactone triol, free radical inhibitor, antioxidant and lubricant, and put into the extrusion equipment for melt blending. After extrusion and cooling, the mixture is granulated to obtain the coating composite masterbatch. S4. After mixing the cyclosiloxane monomer with the end-capping agent, vacuum dehydration is performed. Under inert gas protection, an alkaline catalyst is added, and double-bonded silanes and hydroxyl-containing silanes are slowly added dropwise to carry out a ring-opening copolymerization reaction. After the reaction is completed, an acid is added to neutralize and terminate the reaction. The low-boiling substances and residual monomers are removed by heating and depressurization to obtain the precursor silicone oil. The precursor silicone oil is dissolved in an anhydrous solvent, and diisocyanate and catalyst are added. An addition reaction is carried out under inert gas protection. After the reaction, the solvent and residual free monomers are removed by depressurization to obtain the modified silicone oil. S5. Mix the modified silicone oil, photoinitiator and anhydrous solvent evenly to prepare a photocurable release agent; heat and melt the coating composite masterbatch and extrude it onto the surface of the aminated base paper, cool and shape it to form a coating layer; coat the surface of the coating layer with the photocurable release agent, dry it to remove the solvent and then irradiate it with ultraviolet light; after curing, roll up the release paper and place it in a constant temperature environment to mature, and obtain the finished environmentally friendly release paper.
5. The method for preparing environmentally friendly release paper according to claim 4, characterized in that, Step S1 is specifically performed as follows: Dissolve 2 parts of chitosan in 98 parts of deionized water by weight, add 0.8 parts of glacial acetic acid, and stir until completely dissolved to obtain a chitosan solution; immerse the virgin wood pulp paper in the chitosan solution for 2 minutes, remove it, roll it to remove excess liquid, and dry it at 65±5℃ to make chitosan form a uniform film on the fiber surface, thus obtaining an aminated base paper with a surface rich in primary amino groups.
6. The method for preparing environmentally friendly release paper according to claim 4, characterized in that, Step S2 specifically includes: Step S21: Preparation of double-bond modified calcium carbonate whiskers: 20g of calcium carbonate whiskers with an aspect ratio of 10-20 were ultrasonically dispersed in 200mL of an ethanol / water mixture with a volume ratio of 9:
1. 1.5g of silane coupling agent KH-570 was added, and the pH was adjusted to 4-5 with acetic acid. The mixture was stirred at 60℃ for 2h. After filtration, washing with ethanol, and vacuum drying at 80℃, double-bond modified calcium carbonate whiskers were obtained. Step S22: Synthesis of biodegradable unsaturated copolyester: 0.8 mol succinic acid, 0.2 mol itaconic acid, 1.05 mol 1,4-butanediol and tetrabutyl titanate catalyst at 0.05 mol% relative to the amount of acid were added to the reactor. The esterification reaction was carried out at 180℃ for 2 h under nitrogen protection, followed by polycondensation reaction at 220℃ under reduced pressure for 3 h to obtain poly(butylene succinate-co-butylene itaconic acid).
7. The method for preparing environmentally friendly release paper according to claim 4, characterized in that, Step S3 is as follows: Polylactic acid and polybutylene adipate terephthalate were vacuum dried at 60℃ for 8 hours, biodegradable unsaturated copolyester was vacuum dried at 40℃ for 12 hours, and polycaprolactone triol was vacuum dried at 80℃ for 2 hours and then sealed and cooled. All coating layer raw materials were added to a high-speed mixer and thoroughly mixed. The mixture was then fed into a twin-screw extruder and melt-blended at 150-180℃, extruded and granulated to obtain the coating composite masterbatch.
8. The method for preparing environmentally friendly release paper according to claim 4, characterized in that, Step S4 is as follows: Step S41: By weight, add 100 parts of a dimethylcyclosiloxane mixture and 0.6-0.9 parts of the end-capping agent hexamethyldisiloxane into a reaction vessel, heat to 45°C, dehydrate under a vacuum of -0.095 MPa for 30 min, and purge with nitrogen for protection; add 0.5-1 parts of 2% tetramethylammonium hydroxide alkali gel, stir evenly, and slowly add 14-18 parts of a mixture of 3-(diethoxymethylsilyl)propyl 2-acrylate and 8-12 parts of 3-hydroxypropylmethyldiethoxysilane, and complete the addition in 1 h; after the addition is complete, keep the reaction at 48-50°C for 4.5 h; add glacial acetic acid to neutralize to pH=6.5-7.0, stir for 30 min to terminate the reaction; heat to 125°C, and remove low-boiling substances and residual monomers by vacuum distillation under a vacuum of ≤80 Pa to obtain the precursor silicone oil; Step S42: Dissolve 100 parts by mass of precursor silicone oil in an equal mass of anhydrous ethyl acetate, add isophorone diisocyanate at a -NCO / -OH molar ratio of 1.8-2.2:1, and then add 0.05-0.1 parts of dibutyltin dilaurate catalyst; slowly heat to 60-65℃ under nitrogen protection and stir at a constant temperature for 3-4 hours; after the reaction is completed, evaporate ethyl acetate and residual free monomers under reduced pressure at 60℃ to obtain modified silicone oil.
9. The method for preparing environmentally friendly release paper according to claim 4, characterized in that, Step S5 is as follows: By weight, 100 parts modified silicone oil, 2 parts photoinitiator Irgacure 651, and 40-50 parts anhydrous ethyl acetate are mixed evenly under anhydrous and light-protected conditions to prepare a photocurable release agent. Using a casting coating machine, the coating composite masterbatch is melt-extruded at 170-190℃ and evenly coated onto the surface of the aminated base paper, with the coating thickness controlled at 15-25μm. After cooling and setting, the photocurable release agent is coated onto the surface of the coating layer using an anilox roller, with a wet film thickness of 1-3μm. After drying at 40-50℃ to remove the solvent, it is immediately cured under ultraviolet light. The photocured release paper is then rolled up and placed in a drying oven at 40-50℃ for 24 hours to obtain environmentally friendly release paper.